Changes in Positive and Negative Affect During Pharmacological Treatment and Cognitive Therapy for Major Depressive Disorder: A Secondary Analysis of Two Randomized Controlled Trials. (January 2020) - Dunn, Barnaby D.; German, Ramaris E.; Khazanov, Gabi; Xu, Colin; Hollon, Steven D.; DeRubeis, Robert J.
The cardinal symptoms of major depressive disorder (MDD) are heightened depressed mood (negative affectivity, or NA) and diminished interest or pleasure (positive affectivity, or PA). It is unknown how well treatments for MDD repair either symptom. Two secondary analyses of randomized controlled trials were therefore conducted. In Study 1, 180 adult outpatients with MDD received 16 weeks of antidepressant medication (ADM; n = 120) or cognitive therapy (CT; n = 60). In Study 2, adult outpatients with MDD were treated until remission with ADM ( n = 225) or ADM and CT ( n = 227). Across trials and treatments, intake disturbances were more marked in PA than NA, there was smaller repair of PA than NA during treatment, and disturbances remained more pronounced for PA than NA after treatment. Greater change in PA and NA were independently associated with depression symptom change. These findings suggest that depression treatments more effectively repair NA than PA and that outcomes may be improved with more effective targeting of the latter.